Development of a new wealth index for South Sudan: association between household wealth and malaria prevention practices in the context of seasonal malaria chemoprevention in Northern Bahr el Ghazal, South Sudan - Sikai Huang; Jamshed Khan; Francis Lokang; Abubaker Rom Ayuiel; Kevin Baker; Ahmed Julla; Sol Richardson (Infectious Diseases of Poverty)
Abstract Background The World Health Organization recommends seasonal malaria chemoprevention (SMC) using sulfadoxine-pyrimethamine and amodiaquine (SPAQ) to prevent malaria among children aged 3–59 months in regions with marked seasonality of malaria transmission. Socioeconomic disparities in household malaria prevention within the SMC context remain uncharacterized. This study aimed to construct a household wealth index and examine its association with SMC implementation, children malaria infection, and malaria prevention practices in South Sudan. Methods We utilized data from repeated cross-sectional household surveys conducted in Aweil County in 2022, involving 2767 households. The survey included asset-based questions tailored to the local context. We constructed a 12-item wealth score scale based on asset ownership using Mokken scale analysis and calculated weighted scores using multiple correspondence analysis to obtain wealth index quintiles. Survey-weighted logistic regressions were performed to assess the association of household wealth index quintiles with SMC implementation, children malaria infection, and malaria prevention practices. Results The constructed 12-item wealth scale demonstrated strong internal consistency (Cronbach’s alpha = 0.72). However, households in the lower wealth quintiles (1st quintile) had lower odds of ownership of mosquito nets compared with those in the 3rd quintile [odds ratio (OR) = 0.12, 95% confidence interval (CI): 0.05–0.26, P < 0.001)]. Households in the highest wealth quintile (5th quintile) had higher odds of access to alternative malaria prevention tools (e.g., repellents) compared with the 3rd quintile (OR = 2.75, 95% CI: 1.30–5.83, P = 0.010). However, household wealth was not significantly associated with SMC implementation (household visits by SMC boma distributors, child receipt of Day 1 SPAQ, and caregiver SMC knowledge) or malaria infection outcomes within SMC context. Conclusions The new wealth index tailored to South Sudan is a useful tool for assessing socioeconomic health determinants. While household access to SMC showed a low degree of wealth-associated disparities, reflecting the equitable coverage of the door-to-door SMC delivery model, significant inequities remain in household access to other malaria prevention practices, such as mosquito nets. These findings imply the need for strategies to enhance equity in distributing essential malaria prevention resources. Graphical Abstract